Electrophysiological Characterization of Nicotine-Induced Excitation of Dopaminergic Neurons in the Rat Substantia Nigra - Hiroaki Matsubayashi; Taku Amano; Takahiro Seki; Masashi Sasa; Norio Sakai (Elsevier, 2003)
ABSTRACT: The electrophysiological characteristics of nicotine-induced excitation of dopaminergic neurons in the rat substantia nigra was investigated using the whole-cell patch clamp technique under the voltage-clamp mode. Nicotine (0.01 - 100 μM) induced inward currents corresponding to nicotine-induced depolarization with an increase in firing in a dose-dependent manner. This current was inhibited by dihydro-β-erythroidine, a selective antagonist for the α4β2 type neuronal nicotinic receptor. Nicotine directly acts on postsynaptic α4β2 type nicotinic receptors and induces inward currents, resulting in excitation of dopaminergic neurons in the substantia nigra and subsequent enhancement of dopamine release in the corpus striatum.